2006
DOI: 10.1007/s00262-006-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine gene polymorphisms with malignant melanoma in Caucasian population

Abstract: It has been hypothesized that polymorphisms expected to result in functional changes in cytokine genes may influence susceptibility to cancer, including malignant melanoma (MM). Here, we have screened 24 potentially functional polymorphisms in five cytokine genes by PCR-SBT and PCR-SSP methods in 122 MM cell lines derived from Caucasian patients. The polymorphic positions studied were: TNFA -1031, -863, -857, -851, -574, -376, -308, -238, +488; TGFB1 -988, -800, -509, +869, +915, +652, +673, +713, +788; IL10 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 47 publications
2
33
2
Order By: Relevance
“…Characteristics of the included studies were shown in Table 1. With the exception of 5 studies (Nikolova et al, 2007;Li et al, 2008;Saltzman et al, 2008;Guan et al, 2009;Guo et al, 2011), the distribution of genotypes for the C-509T polymorphism in the controls of all studies was consistent with Hardy-Weinberg equilibrium. Quantitative Data Synthesis Overall, there was no association between TGF-β1 C-509T polymorphism and cancer risk in all genetic models (T vs. C: OR=1.01, 95%CI=0.94-1.07; TT vs. CC: OR=1.01, 95%CI=0.89-1.15; CT vs. CC: OR=0.98, 95%CI=0.90-1.06; CT+TT vs. CC: OR=0.98, 95%CI=0.88-1.08; TT vs. CT+CC: OR=1.00, 95%CI=0.91-1.10; Table 2).…”
Section: Characteristics Of Studiesmentioning
confidence: 73%
“…Characteristics of the included studies were shown in Table 1. With the exception of 5 studies (Nikolova et al, 2007;Li et al, 2008;Saltzman et al, 2008;Guan et al, 2009;Guo et al, 2011), the distribution of genotypes for the C-509T polymorphism in the controls of all studies was consistent with Hardy-Weinberg equilibrium. Quantitative Data Synthesis Overall, there was no association between TGF-β1 C-509T polymorphism and cancer risk in all genetic models (T vs. C: OR=1.01, 95%CI=0.94-1.07; TT vs. CC: OR=1.01, 95%CI=0.89-1.15; CT vs. CC: OR=0.98, 95%CI=0.90-1.06; CT+TT vs. CC: OR=0.98, 95%CI=0.88-1.08; TT vs. CT+CC: OR=1.00, 95%CI=0.91-1.10; Table 2).…”
Section: Characteristics Of Studiesmentioning
confidence: 73%
“…9 Previous reports showed that reduced levels of IL10 have been associated with the presence of the IL10 À1082G/À819T/À592A haplotype on the IL-10 gene promoter 10,11 as well as with increased risk of cancer in several populations. 12,13,14 Hence, in recent studies, three common polymorphisms in the promoter of the IL-10 gene, À1082 (rs1800896) A4G, À819 (rs1800871) C4T and À592(rs1800872) C4A, have been extensively studied in PCa. 15 However, results of studies that examined the association of the three singlenucleotide polymorphisms (SNPs) to the incidence of PCa have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…20,32,33 Indeed, this is in line with most other publications regarding IL-10 polymorphisms and melanoma. [22][23][24][26][27][28] In contrast, Nagano et al 34 reported that 'low-expression' IL-10 polymorphisms significantly protected from non-melanoma skin cancer. This may indicate that the effects of IL-10 differ in different skin cancer entities.…”
Section: Methodsmentioning
confidence: 98%
“…However, IL-10 low-producing haplotypes like ACC/ATA were associated with a shorter survival time and greater tumour thickness. Similarly, Nikolova et al 23 reported that the low-producing haplotypes like ATA were significantly increased in melanoma cell lines compared with controls, suggesting an association with melanoma susceptibility. Finally, Howell et al 24 found that the IL-10 À1087AA lowexpression genotype was significantly increased among melanoma patients compared with controls.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation